Factors Associated with Depression in Elderly Peritoneal Dialysis Patients - Sindhu, Sirion; Varitsakul, Rotsukon; Sriyuktasuth, Aurawamon (Nursing Science Journal of Thailand, 2011)
Purpose: Depression is a common emotional problem of elderlypatients whose their physical and psychosocial limitations wouldobstacle the peritoneal dialysis (PD) performance. This study wasaimed to investigate the prevalence of depression and therelationships between depression and socio-demographic factors,dialysis time, hospitalization, comorbidity, and level of activity indaily living of elderly PD patients. Design: A cross-sectional descriptive study. Methods: A convenient sample of 100 participants was recruitedfrom 20 Dialysis units located in Central and Northern eastregion during June-December 2010. The patient’s demographicdata assessment, the Charlson’s Comorbid Index, the Katz Index,and 9-Item Thai Patient Health Questionnaire were used in thestudy. Data were analyzed by using the Chi-square and Pearson’scorrelation statistics. Main findings: The results found that the prevalence ofdepression in elderly PD patients was 31%. There were significantrelationships between depression and occupation factor andhaving a PD caregiver factor (X2 = 12.011, p = .001, X2 = 6.840,p = .009 respectively). Moreover, age, comorbidity and level ofactivity in daily living were moderately associated withdepression in elderly PD patients (r = .386, p < .001, r = .339,p < .001, r = - .467, p < .001 respectively). Conclusion and recommendations: These results provideinformation used to reduce and prevent depressive symptoms inorder to effectively deliver the PD service to the patients.